2015
DOI: 10.1088/0143-0807/36/5/055017
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the electron transport in semiconductors via Monte Carlo simulations: an inquiry-driven learning path for engineering undergraduates

Abstract: Within the context of higher education for science or engineering undergraduates, we present an inquiry-driven learning path aimed at developing a more meaningful conceptual understanding of the electron dynamics in semiconductors in the presence of applied electric fields. The electron transport in a nondegenerate n-type indium phosphide bulk semiconductor is modelled using a multivalley Monte Carlo approach. The main characteristics of the electron dynamics are explored under different values of the driving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Different SPH models of surface tension have been recently discussed in the literature [4,9,20,25]. Among these, the so-called interparticle force model is in our 1 The equations of motion of these particles in the liquid are determined by the continuum equations of fluid dynamics with interpolation from the particles, which have, therefore, to be partially overlapping. opinion better suitable for didactical purpose because of its simplicity and easiness of implementation in computer code.…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Different SPH models of surface tension have been recently discussed in the literature [4,9,20,25]. Among these, the so-called interparticle force model is in our 1 The equations of motion of these particles in the liquid are determined by the continuum equations of fluid dynamics with interpolation from the particles, which have, therefore, to be partially overlapping. opinion better suitable for didactical purpose because of its simplicity and easiness of implementation in computer code.…”
Section: The Modelmentioning
confidence: 99%
“…As it is well-known, computer-based modeling environments can supply students with effective pedagogical strategies dealing with complex real-world systems and everyday problem solutions [1,3,6,10,19]. Research has shown that computer simulations can efficiently raise student's interest in learning by vivid graphical construction and animation [12,24] and be used to help students to gain insights into phenomena and overcome mathematical difficulties [14].…”
Section: Introductionmentioning
confidence: 99%
“…The electron transport dynamics is simulated by a semiclassical Monte Carlo algorithm, which takes into account all the possible scattering events of the hot electrons in the medium [154,155] and includes the precession equation of the spin polarisation vector for each free carrier [149,156,157]. The Monte Carlo algorithm has been implemented by using a Multiparticle Multivalley FORTRAN Code, following the procedure extensively described in [158].…”
Section: Monte Carlo Approach and Noise Modellingmentioning
confidence: 99%
“…They suggest that the active learning experience should replace the lecture as a dominant mode including laboratory activities, internships, and cooperative learning [16,36]. Moreover, designing an active learning environment requests the acceptance of the concept that practice helps theoretical learning provided that there is a high level of integration between lectures and practice [21,22,42,59].…”
Section: Introductionmentioning
confidence: 99%